2020
DOI: 10.1039/c9ta13069a
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-highly conductive hollow channels guided by a bamboo bio-template for electric and electrochemical devices

Abstract: Bamboo-based devices! A new method to fabricate silver conductive coatings into the inner walls of bamboo vascular bundles is disclosed. The hollow conductive microchannels enabled the development of new electrical and electrochemical devices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
13
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 65 publications
0
13
0
6
Order By: Relevance
“…Based on the enlightenment from this perspective, the concept of morphology genetic materials (MGMs) has been proposed in recent years, focusing on the functionalization of materials while preserving the morphological structure of the organism itself [ 10 ]. In past few years, it has been found that the carbon skeleton of plants, animals, or microorganisms obtained by carbonization treatment at high temperature has the potential to be a good EMW absorber [ 11 ]. Moreover, introducing some special structural treatment methods in the preparation process can effectively enhance the absorption performance.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the enlightenment from this perspective, the concept of morphology genetic materials (MGMs) has been proposed in recent years, focusing on the functionalization of materials while preserving the morphological structure of the organism itself [ 10 ]. In past few years, it has been found that the carbon skeleton of plants, animals, or microorganisms obtained by carbonization treatment at high temperature has the potential to be a good EMW absorber [ 11 ]. Moreover, introducing some special structural treatment methods in the preparation process can effectively enhance the absorption performance.…”
Section: Introductionmentioning
confidence: 99%
“…These advantages allow us to design ideal materials for different purposes through different experimental methods. MOFs are also used in a wide variety of applications including gas separation [5,6], sensing [7], gas adsorption [8,9], selective catalysis [10,11], ion exchange [12], ultra-high purity separation [13], protein hydrolysis [14], as well as in biological conductive materials, photoelectric materials, new semiconductor materials, magnetic materials and in the field of chip development [15][16][17][18][19]. With this vast array of possibilities, high expectations have been laid on MOFs and its composite materials.…”
Section: Introductionmentioning
confidence: 99%
“…23 Diversos estudos já mostraram a versatilidade desse material que já foi empregado em construções, 24 encanamentos, 25 tecidos, 26 dispositivos químicos 27 e elétricos. 28 É um material facilmente modificável, barato e de rápido crescimento. Além disso, devido à sua constituição, é um material extremamente leve, flexível e muito resistente, sendo chamado até de aço vegetal.…”
Section: Introductionunclassified
“…30,31 Existem diversos tratamentos de modificação da celulose, o que abre uma gama de possibilidades para a utilização de materiais lignocelulósicos para os mais diversos fins. Além disso, os canais vasculares do bambu, da ordem de dezenas a centenas de micrometros, retos e paralelos entre si, também encontram aplicações em outras áreas, como na microfluídica, 28,33 por exemplo.…”
Section: Introductionunclassified
See 1 more Smart Citation